1992
DOI: 10.1088/0029-5515/32/9/i07
|View full text |Cite
|
Sign up to set email alerts
|

Density fluctuation measurements in ATF using correlation reflectometry

Abstract: A two-frequency correlation reflectometer has been operated on the Advanced Toroidal Facility (ATF) to measure plasma electron density fluctuations. This reflectometer uses quadrature phase detection to permit true phase measurement of the reflected microwave signal (probing beam). By measuring the phase fluctuations in the reflected probing beam, the amplitude of the density fluctuations can be estimated. Simultaneous two-frequency operation makes it possible to measure the coherence between fluctuations at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…This so called ''phase runaway'' has been observed for many plasma conditions with almost all reflectometers. [1][2][3][4][5][6] It has been suggested that it is a Doppler shift of the probing radiation reflected from rotating cutoff layer disturbances. 2,4,5,7 Either these disturbances are asymmetric or a misalignment of the reflectometer axis with respect to the normal at the cutoff layer exists.…”
Section: Introductionmentioning
confidence: 99%
“…This so called ''phase runaway'' has been observed for many plasma conditions with almost all reflectometers. [1][2][3][4][5][6] It has been suggested that it is a Doppler shift of the probing radiation reflected from rotating cutoff layer disturbances. 2,4,5,7 Either these disturbances are asymmetric or a misalignment of the reflectometer axis with respect to the normal at the cutoff layer exists.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the reemergence of microwave reflectometry as a diagnostic with good resolution for long wavelength fluctuations. [83][84][85][86][87][88][89][90][91][92][93][94][95] In this paper, we review the application of microwave reflectometry to the measurement of density profiles and to the detection of density fluctuations in magnetically confined plasmas. The paper is organized as follows: Section II is a brief review of the theory of plasma waves that are of interest for reflectometry in magnetized plasmas, i.e., those in the electron cyclotron range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the results reported here have been observed in experimental signals-indeed there is now a substantial body of evidence in the literature (e.g. [14][15][16][17][18][19][21][22][23]). However, it is beyond the scope of this paper to include an experimental example for each simulation result (space limitations notwithstanding) but where possible reference will be made to examples in the literature.…”
Section: G D Conwaymentioning
confidence: 79%
“…It has been widely suggested that asymmetry or misalignment between the launch and receive antennae and the plasma reflection layer may be responsible for the ubiquitous phase runaway effect observed in many experiments [14][15][16][17][18][19][20]. Indeed, recent simulations using 2D…”
Section: Introductionmentioning
confidence: 99%